ASIMETRI INFORMASI PADA EMITEN SYARIAH DAN DAMPAKNYA TERHADAP MANAJEMEN LABA - Muslim, Ade Imam; Widyastuti, Tri (Universitas Pendidikan Indonesia, 2019)
Abstract. Earnings information is very important for investors in their decision-making process to enter in a capital market. Informations are very important for investors, asymmetry information is never expected by any investor. Asymmetry information is as well, a serious concern for regulators of capital markets. This study aims to determine the effect of asymmetry information on the presence or absence of earnings management practices in Sharia-based bonds and stocks issuers. Through 20 companies listed on the Jakarta Islamic Index we analysed, we found out that asymmetry information has no effect on earnings management on Sharia-based bonds and stocks issuers. In addition, we also did not find sufficient evidence that justify that Sharia-based bonds and stocks issuers practice earnings management.Keywords: asymmetry information; earnings managementAbstrak. Informasi laba sangat penting bagi investor yang akan memasuki pasar modal. Begitu pentingya informasi bagi investor sehingga asimetri informasi tidak diharapkan oleh para investor. Informasi asimetri juga menjadi perhatian serius dari para regulator dan pasar modal. Penelitian ini bertujuan untuk mengetahui pengaruh asimetri informasi terhadap ada tidaknya praktik manajemen laba di emiten syariah. Melalui 20 emiten yang dianalisis, kami menemukan bahwa asimetri informasi tidak berpengaruh terhadap manajemen laba pada emiten syariah. Selain itu, kami juga tidak menemukan bukti yang cukup kuat untuk menjustifikasi bahwa emiten syariah melakukan praktik manajemen laba.Kata Kunci: asimetri informasi; manajemen laba.